The Influence of Young Teachers' and Professional Teachers' Learning Skills on Student Learning Outcomes at SDN 33 Bangai, Torgamba District, South Labuhanbatu Selatan - Syafnan; Juli AZMI; Rika Andriani Ritonga (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This aiming For analyze influence skills teaching young teachers and professional teachers to results Study students at SD Negeri 33 Bangai . Using approach quantitative comparative with design ex post facto , data collected through test academic , observation skills teaching , and documentation mark students . The sample consists of from two classes , each taught by a teacher with background behind experience different . Analysis results show that despite average skills teaching young teachers and professional teachers similar , there are difference significant in aspect its implementation . Young teacher superior in use of digital learning media and building interaction , while professional teachers show superiority in management class and delivery systematic material . Average value student classes taught by professional teachers A little more high and consistent . Research This conclude that second teacher group contributes positive to results learn , with characteristics different strengths . Collaboration​ intergenerational teacher support is recommended as a strategy for optimize quality learning at school base